2020
DOI: 10.1039/d0cp00652a
|View full text |Cite
|
Sign up to set email alerts
|

Optimum in the thermoelectric efficiency of nanostructured Nb-doped TiO2ceramics: from polarons to Nb–Nb dimers

Abstract: Thermoelectric properties of bulk nanostructured Nb-doped rutile TiO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 81 publications
3
11
0
Order By: Relevance
“…While TN30 exhibits the highest power factor of 470 μW m –1 K –2 at room temperature, the ZT value was only 0.04 due to the relatively high thermal conductivity; nevertheless, this is still the highest ZT value at room temperature. At elevated temperatures, the ZT values increase with increasing Nb content, to a maximum value of 0.17 for TN60 at 873 K. The ZT values from this study are presented graphically alongside data from other studies ,, , for single Nb-doped TiO 2 -based thermoelectric ceramics in Figure b. The present results show approximately 50% enhancement in ZT at 373 K compared with earlier studies.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…While TN30 exhibits the highest power factor of 470 μW m –1 K –2 at room temperature, the ZT value was only 0.04 due to the relatively high thermal conductivity; nevertheless, this is still the highest ZT value at room temperature. At elevated temperatures, the ZT values increase with increasing Nb content, to a maximum value of 0.17 for TN60 at 873 K. The ZT values from this study are presented graphically alongside data from other studies ,, , for single Nb-doped TiO 2 -based thermoelectric ceramics in Figure b. The present results show approximately 50% enhancement in ZT at 373 K compared with earlier studies.…”
Section: Resultssupporting
confidence: 63%
“…At elevated temperatures, the ZT values increase with increasing Nb content, to a maximum value of 0.17 for TN60 at 873 K. The ZT values from this study are presented graphically alongside data from other studies 1,12,[54][55][56]61 for single Nb-doped TiO 2 -based thermoelectric ceramics in Figure 11b. The present results show approximately 50% enhancement in ZT at 373 K compared with earlier studies.…”
Section: ■ Results and Discussionmentioning
confidence: 65%
“…The EXAFS results also indicate that it is unlikely that Nb forms dimers as has been postulated in some Nb-doped TiO 2 . 33 In other studies, anatase thin films were prepared from a composite TiNb target by reactive magnetron sputtering giving a level of 1.5% Nb doped in TiO 2 anatase. 29 The authors conclude that “the local environment of Nb atoms in the film is close to that of Ti atoms in the anatase phase [...].…”
Section: Resultsmentioning
confidence: 99%
“…A good TE efficiency requires materials with low thermal conductivity and high electrical conductivity. While a small amount of Nb (2-4 at.%) increases the electrical conductivity of TiO 2 by several orders of magnitude, it has been recently shown that the thermal conductivity of bulk nano-structured Nb-TiO 2 obtained by spark plasma sintering (SPS) is significantly lowered by decreasing the average grain size [1]. A value of 2.5 W/mK has been observed at 900 K for an average grain size of 170 nm, while the value in the single crystal is of about 4 W/mK.…”
Section: Introductionmentioning
confidence: 99%